Geographical mapping and seroprevalence of Burkholderia pseudomallei amongst livestock species in Lao People's Democratic Republic. - Suwei Zheng; James R Young; Syseng Khounsy; Phouvong Phommachanh; Peter Christensen; Watthana Theppangna; Tom Hughes; Adisone Temmerath; Alex Inthavong; Phoummavanh Inthapanya; Sivone Panyasith; Koukeo Phommasone; et al. (PLoS Neglected Tropical Diseases)
The Gram-negative bacterium Burkholderia pseudomallei causes a severe infectious disease known as melioidosis in humans and animals. It is considered endemic in tropical countries, including Thailand, Lao PDR (Laos), and Northern Australia. B. pseudomallei is a saprophyte found in contaminated soil and surface water. Humans and animals can become infected via direct exposure to contaminated water or soil and inhalation of dust or water droplets. Despite the high morbidity and mortality rates of melioidosis, there is a lack of knowledge of its geographical distribution and seroprevalence, even within endemic countries, raising a significant public health concern. For a better understanding of melioidosis in livestock in Laos, both as an animal health concern and as an indicator of human risk, we collected serum samples from an abattoir monitoring program for B. pseudomallei antibody testing using the Indirect Haemagglutination Assay (IHA). Out of the 917 sera collected, major findings included the identification of a significant cluster (p = 0.041) in the southwest border region adjoining northeastern Thailand, in the province of Savannakhet in Laos. Sera collected in January 2020 had the highest B. pseudomallei seroprevalence (17.0%), and cattle had the highest seroprevalence (22.8%), followed by buffalo (19.7%) and swine (4.0%). The B. pseudomallei seroprevalence results among the common livestock species and the maps generated can assist with future monitoring, prevention, and detection of melioidosis in Laos.